Evaluation of BMS-986142, a reversible Bruton's tyrosine kinase inhibitor, for the treatment of rheumatoid arthritis: a phase 2, randomised, double-blind, dose-ranging, placebo-controlled, adaptive design study. (May 2023) - Conaghan, Philip G; Nowak, Miroslawa; Du, Shuyan; Luo, Yi; Landis, Jessica; Pachai, Chahin; Fura, Aberra; Catlett, Ian M; Grasela, Dennis M; Østergaard, Mikkel
Summary: Background: Bruton's tyrosine kinase (BTK) is a promising biological target for rheumatoid arthritis treatment. This study examined safety, efficacy, and pharmacokinetics of BMS-986142, an oral, reversible BTK inhibitor. The aim was to compare the efficacy of BMS-986142 with placebo on a background of methotrexate in patients with moderate-to-severe rheumatoid arthritis and inadequate response to methotrexate. Methods: This phase 2, randomised, double-blind, dose-ranging, placebo-controlled, adaptive design study was conducted across 14 countries and 79 clinical sites. We recruited people aged 18 years or older with a documented diagnosis of rheumatoid arthritis at least 16 weeks before screening with an inadequate response to methotrexate with or without inadequate response to up to two tumour necrosis factor inhibitors. Participants were randomly assigned (1:1:1:1) to oral BMS-986142 (100 mg, 200 mg, or 350 mg) or placebo once daily for 12 weeks. Randomisation was done using an interactive voice response system and stratified by prior treatment status and geographical region. All participants, care providers, investigators, and outcome assessors were masked to treatment allocation. Co-primary endpoints were 20% and 70% improvement in American College of Rheumatology criteria (ACR20 and ACR70) at week 12. Primary endpoints were assessed in the efficacy analysis population (all randomised patients who received at least one dose of the study drug and did not discontinue the study). Safety endpoints were analysed in the as-treated analysis population, which included all patients who received at least one dose of the study drug (patients were grouped according to the treatment they actually received vs the treatment to which they were randomised). This trial was registered with ClinicalTrials.gov, number NCT02638948 . Findings: Between Feb 24, 2016 and May 3, 2018, 248 patients were randomised (73 in the BMS-986142 100 mg group, 73 in the 200 mg group, 26 in the 350 mg group, and 75 in the placebo group; one post-randomisation exclusion); mean age was 56·7 years (SD 12·7); 214 (87%) of 247 were women, 33 (13%) were men, and 188 (76%) were White. Pre-specified interim analysis resulted in discontinuation of the 350 mg BMS-986142 dose due to elevated liver enzymes and absence of benefit versus placebo. Co-primary endpoints were not met. Response rates for ACR20 (placebo: 23 [31%] of 75; 100 mg: 26 [36%] of 73; 200 mg: 31 [42%] of 73) and ACR70 (placebo: three [4%] of 75; 100 mg: three [4%] of 73; 200 mg: seven [10%] of 73) were not significantly different to placebo; estimate of difference versus placebo for ACR20 was 4·9 (95% CI –10·2 to 20·1; p=0·52) for 100 mg and 11·8 (–3·6 to 27·2; p=0·14) for 200 mg, and for ACR70 the estimate of difference was 0·1 (–16·0 to 16·5; nominal p=1·00) for 100 mg and 5·6 (–10·5 to 21·9; nominal p=0·21) for 200 mg. Six patients experienced serious adverse events (four in the placebo group [mouth ulceration, open globe injury, rheumatoid arthritis flare, and endometrial adenocarcinoma] and two in the BMS-986142 100 mg group [angina pectoris and intestinal obstruction]); there were no deaths. Interpretation: Further investigation of BMS-986142 in people with rheumatoid arthritis is not warranted. An absence of clinical benefit in this study, together with other study results, highlights the need for additional research on the extent of BTK inhibition, treatment duration, and adequacy of drug distribution to inflammation sites, to understand the potential utility of BTK inhibition as a therapeutic strategy for rheumatoid arthritis. Funding: Bristol Myers Squibb.